Multilayer composite polyimide material and preparation method and application thereof
By using multi-layer composite polyimide materials in polyimide copper-clad laminates and combining the properties of thermoplasticity and transparent polyimide, the bonding of polyimide copper-clad laminates under high-temperature welding conditions in the existing technology is solved. The problems of reduced strength, thermal expansion coefficient mismatch and poor dimensional stability are achieved by achieving high heat resistance and dimensional stability of the material.
Patent Information
- Application Number
- CN202310251420.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-03-16
AI Technical Summary
The existing polyimide copper clad plates have problems such as reduced bond strength, mismatch of thermal expansion coefficient and poor dimensional stability under high temperature welding conditions, which limits their application in flexible printed circuit boards.
Multi -layer composite polytamide material includes two layers of thermoplastic polybinamidide and transparent polytamide. Through specific molecular structure design and polymerization reaction conditions, the adhesion performance, thermal expansion coefficient matching of the item, and Size stability.
The high heat resistance, good size stability, and the thermal expansion performance of the copper foil are realized, and the thermal expansion performance of the copper foil is improved, and the adhesion strength and the reliability of high temperature welding of the copper -covered plate are improved.
Smart Images

Figure CN116478436B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer synthesis, and in particular to a multilayer composite polyimide material and a preparation method and application thereof. Background Art
[0002] Polyester flexible copper clad laminate PET-FCCL is a relatively mature type of transparent FCCL product on the market. It is mainly made of PET as the insulating base film, adhesive and conductive layer copper foil laminated together, and is used in antennas of various electronic devices, automotive instruments, household appliances, electronic toys and computer-aided equipment, etc. The three-layer PET-FCCL is prepared by coating a layer of transparent adhesive on the surface of the PET film and then laminating it with copper foil. PET-FCCL has excellent optical transmittance after etching, but because the melting point of PET is around 250°C and its heat resistance is poor, it cannot be used in the surface assembly technology (SMT) process of flexible printed circuit boards (FPCs). The SMT welding temperature is generally above 260°C, so it can only be used for low-temperature welding, which limits the application of PET in higher-end products.
[0003] With the rapid development of polymers, flexible transparent polyimide (PI) has begun to attract attention. In addition to maintaining the high heat resistance and high bendability of polyimide itself, the high optical transmittance of PI film makes it more widely used in many high-tech fields. For example, in flexible OLED displays, transparent polyimide (CPI) will be used as an optically transparent film for transparent flexible substrates, touch substrates, under-screen camera covers, and mobile phone covers. In the field of microelectronics, polyimide is mainly widely used as an insulating base film for flexible printed circuits.
[0004] Specifically, flexible printed circuits are usually divided into two types of flexible copper clad laminates: three-layer adhesive type and double-layer adhesive-free type. Among them, the three-layer adhesive flexible copper clad laminate is composed of copper foil, adhesive and polyimide film. The traditional flexible copper clad laminate uses yellow transparent polyimide film as the substrate. Due to the color limitation of PI film, this FCCL cannot be applied to colorless transparent flexible circuit boards. Therefore, colorless transparent polyimide must be used as the substrate of FCCL. In addition, the adhesive in the copper clad laminate mainly uses epoxy resin or acrylic resin. When the temperature is higher than 150°C, the peel strength is greatly reduced due to the deterioration of the adhesive. When welding on the flexible board, the temperature mostly exceeds 300°C. In addition, the flexible copper clad laminate containing adhesive may also have problems such as thick insulation layer, poor heat resistance and high thermal expansion coefficient. In addition, the dimensional change rate of the three-layer adhesive flexible copper clad laminate is greatly affected by temperature, poor dimensional stability, and poor chemical corrosion resistance. The double-layer flexible copper clad laminate does not contain adhesive and is composed only of copper foil and polyimide film. Therefore, it has better heat resistance, dimensional stability, flame retardancy and chemical corrosion resistance. However, the polyimide that can be used in adhesive-free copper clad laminates is not only required to match the thermal expansion coefficient of the copper foil, but also to have a sufficiently high bonding strength with the copper foil. There are few polyimides that meet these requirements. Summary of the invention
[0005] Based on this, the present invention provides a multilayer composite polyimide material, which has high optical transparency, a thermal expansion coefficient that matches that of copper foil, and high bonding strength with the copper foil.
[0006] The technical solution is as follows:
[0007] A multi-layer composite polyimide material, the structure of which includes a first layer and a second layer arranged in layers;
[0008] The first layer comprises thermoplastic polyimide (TCPI);
[0009] The second layer comprises transparent polyimide (CPI);
[0010] The thermoplastic polyimide has a structure shown in formula (1-1):
[0011]
[0012] Z is an alkyl group;
[0013] X is
[0014] R1 is selected from a single bond or a group as shown below:
[0015]
[0016] Each R2 is independently selected from non-existent, chain alkyl, cycloalkyl, fluoroalkyl, ester or halogen;
[0017] Y is selected from the group shown below:
[0018]
[0019] R3, R5 and R6 are independently selected from non-existent, chain alkyl, cycloalkyl, fluoroalkyl, ester or halogen;
[0020] R4 and R7 are independently selected from a single bond or a group as shown below:
[0021]
[0022] The structural unit of the transparent polyimide has a structure shown in formula (2-1):
[0023]
[0024] in,
[0025] Ar1 is selected from any of the following groups:
[0026]
[0027] R8 and R9 are each independently selected from a single bond or a group as shown below:
[0028]
[0029] and at least one of R8 and R9 is R 10 and R 11 are independently selected from non-existent, chain alkyl, cycloalkyl, fluoroalkyl, ester or halogen; Ar3 is an alicyclic ring with 6 to 20 ring atoms, or an aromatic ring with 6 to 20 ring atoms;
[0030] Ar2 is selected from any of the following groups:
[0031]
[0032] Each R 12 Each R is independently selected from non-existent, chain alkyl, cycloalkyl, fluoroalkyl, ester or halogen; 13 Each is independently selected from the following groups:
[0033]
[0034] M is selected from *O* or *S*;
[0035] m represents the degree of polymerization;
[0036] n, p and r are each independently selected from any integer between 1 and 10.
[0037] * indicates the attachment site.
[0038] In one embodiment, Z is a C1-C20 straight chain alkyl group, a C1-C20 branched chain alkyl group, or a C3-C20 cycloalkyl group.
[0039] In one embodiment, R2, R3, R5 and R6 are independently selected from C1-C10 straight chain alkyl, C1-C10 branched chain alkyl, C3-C10 cycloalkyl, C1-C10 fluoroalkyl or halogen.
[0040] In one embodiment, the R 10 , R 11 and R 12 Each is independently selected from C1-C10 straight-chain alkyl, C1-C10 branched-chain alkyl, C3-C10 cycloalkyl, C1-C10 fluoroalkyl or halogen.
[0041] In one embodiment, Ar3 is a benzene ring, a naphthalene ring or a cyclohexane ring.
[0042] In one embodiment, m is from 1 to 1000.
[0043] In one embodiment, the thickness of the first layer is 1 μm to 20 μm, and the thickness of the second layer is 30 μm to 100 μm.
[0044] In one of the embodiments, the multi-layer composite polyimide material further includes a third layer;
[0045] Along a direction away from the first layer, the third layer and the second layer are stacked;
[0046] The third layer comprises a thermoplastic polyimide as described above.
[0047] In one embodiment, the thickness of the third layer is 1 μm to 20 μm.
[0048] The present invention also provides a method for preparing the multilayer composite polyimide material as described above, comprising the following steps:
[0049] A diamine having a structure of formula (I), a primary amine having a structure of formula (II) and a dianhydride having a structure of formula (III) are mixed in a first organic solvent, subjected to a first polymerization reaction, and subjected to dehydration and cyclization to prepare a thermoplastic polyimide represented by formula (1-1);
[0050] H2N-Y-NH2(I), Z-NH2(II),
[0051] Mixing a diamine having a structure of formula (IV) and a dianhydride having a structure of formula (V) in a second organic solvent, performing a second polymerization reaction, and performing dehydration cyclization to prepare a transparent polyimide having a structural unit having a structure represented by formula (2-1);
[0052] H2N-Ar2-NH2(IV),
[0053] Performing composite molding treatment on the transparent polyimide and the thermoplastic polyimide;
[0054] Ar1, Ar2, X, Y and Z are as defined above.
[0055] In one embodiment, the molar ratio of the diamine having the structure of formula (I) to the primary amine having the structure of formula (II) is: (90-99): (1-10);
[0056] The molar ratio of the total molar amount of the diamine having the structure of formula (I) and the primary amine having the structure of formula (II) to the dianhydride having the structure of formula (III) is 100:(100-110).
[0057] In one embodiment, the temperature of the first polymerization reaction is 50° C. to 200° C., and the time is 0.1 h to 12 h.
[0058] In one embodiment, the diamine having the structure of formula (I) is selected from the diamine compounds shown below:
[0059]
[0060]
[0061] The primary amine having the structure of formula (II) is selected from ethylamine, propylamine, isopropylamine, n-butylamine, isobutylamine, 2-aminobutane, 2-amino-2-methylpropane, pentylamine, isopentylamine, n-hexylamine, n-heptylamine, n-octylamine, n-nonylamine, n-decylamine, 1-aminododecane, n-tridecylamine, stearylamine, 2-cyclohexylethylamine or (3-aminopropyl)cyclohexane; and / or
[0062] The dianhydride having the structure of formula (III) is selected from the dianhydride compounds shown below:
[0063]
[0064] In one embodiment, the molar ratio of the diamine having the structure of formula (IV) to the dianhydride having the structure of formula (V) is (95-105):100.
[0065] In one embodiment, the temperature of the second polymerization reaction is below 60° C., and the time is 0.1 h to 30 h.
[0066] In one embodiment, the diamine having the structure of formula (IV) is selected from the diamine compounds shown below:
[0067]
[0068]
[0069] The dianhydride having the structure of formula (V) is selected from the dianhydride compounds shown below:
[0070]
[0071] In one embodiment, the composite molding process comprises the following steps:
[0072] preparing a thermoplastic polyimide solution;
[0073] coating the thermoplastic polyimide solution on the surface of the transparent polyimide;
[0074] drying.
[0075] The present invention also provides an insulating base film, which comprises the multi-layer composite polyimide material as described above, or the multi-layer composite polyimide material prepared according to the preparation method as described above.
[0076] The present invention also provides a copper clad laminate, which comprises the multi-layer composite polyimide material as described above, or the multi-layer composite polyimide material prepared according to the preparation method as described above, or the insulating base film as described above.
[0077] The present invention also provides a rigid printed circuit board, which comprises the multilayer composite polyimide material as described above, or the multilayer composite polyimide material prepared according to the preparation method as described above, or the insulating base film as described above, or the copper clad plate as described above.
[0078] The present invention also provides a flexible printed circuit board, which comprises the multilayer composite polyimide material as described above, or the multilayer composite polyimide material prepared according to the preparation method as described above, or the insulating base film as described above, or the copper clad plate as described above.
[0079] The present invention has the following beneficial effects:
[0080] The multilayer composite polyimide material provided by the present invention comprises a thermoplastic polyimide shown in formula (1-1) and a polyimide shown in formula (2-1). Wherein, the molecular chain end of the thermoplastic polyimide shown in formula (1-1) contains an alkyl group and a specific amide group, which can improve the dielectric properties and bonding properties of the multilayer composite polyimide material. The polyimide molecule shown in formula (2-1) contains an amide bond and a fluorene group structure, and the amide bond can form hydrogen bonds between the molecular chains, thereby forming a hydrogen bond cross-linked network, promoting the in-plane orientation of the molecular chains and enhancing the interaction force between the molecular chains, thereby reducing the thermal expansion coefficient, increasing the glass transition temperature, and improving the transparency and dimensional stability of the polyimide; the fluorene group with a large steric hindrance effect can increase the rotational kinetic energy of the polyimide molecular chain, limit the movement of the chain segments, greatly increase the glass transition temperature, and improve the transparency and dimensional stability of the polyimide. The thermoplastic polyimide shown in formula (1-1) and the polyimide shown in formula (2-1) cooperate with each other, so that the multilayer composite polyimide material provided by the present invention has excellent heat resistance, thermal expansion properties matching those of copper foil, good dimensional stability, and high bonding strength with copper foil.
[0081] Using the above-mentioned multi-layer composite polyimide material to prepare adhesive-type copper-clad laminates can effectively reduce the thickness of traditional adhesive-type copper-clad laminates and solve the problems of delamination and bubbles in copper-clad laminates during soldering and high-temperature applications.
[0082] In addition, the preparation method of the multilayer composite polyimide material provided by the present invention is simple in process, safe, and suitable for scaled-up production. BRIEF DESCRIPTION OF THE DRAWINGS
[0083] Figure 1 A schematic diagram of the structure of a double-layer composite polyimide material according to an embodiment of the present invention;
[0084] Figure 2 A schematic diagram of the structure of a three-layer composite polyimide material according to an embodiment of the present invention;
[0085] Figure 3 A schematic diagram of the structure of a single-sided copper clad laminate according to an embodiment of the present invention;
[0086] Figure 4 A schematic diagram of the structure of a double-sided copper clad laminate according to an embodiment of the present invention; DETAILED DESCRIPTION
[0087] The present invention will be further described below in conjunction with the embodiments and examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the protection scope of the appended claims of the present invention.
[0088] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0089] the term
[0090] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:
[0091] The terms "and / or", "or / and", and "and / or" used in the present invention include any one of two or more related listed items, and also include any and all combinations of related listed items, wherein the any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that in the present invention, the technical solution undoubtedly includes technical solutions connected by "logical and", and also undoubtedly includes technical solutions connected by "logical or". For example, "A and / or B" includes three parallel solutions of A, B and A+B. For example, the technical solution of "A, and / or, B, and / or, C, and / or, D" includes any one of A, B, C, and D (that is, the technical solution that is all connected by "logical OR"), and also includes any and all combinations of A, B, C, and D, that is, the combination of any two or any three of A, B, C, and D, and also includes the combination of four of A, B, C, and D (that is, the technical solution that is all connected by "logical AND").
[0092] In the present invention, "multiple" means at least two, such as two, three, etc., and "multi-layer" means at least two layers, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present invention, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0093] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0094] In the present invention, “preferred”, “better”, “better”, etc. are only used to describe implementation methods or examples with better effects. It should be understood that they do not constitute limitations on the scope of protection of the present invention.
[0095] In the present invention, “further”, “furthermore”, “particularly”, etc. are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present invention.
[0096] In the present invention, in "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", "the fifth aspect", etc., the terms "first", "second", "third", "fourth", "fifth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", "fifth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0097] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0098] In the present invention, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when a numerical interval only refers to an integer within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be merged. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all subranges included therein.
[0099] In the present invention, the number of atoms described by a numerical range includes both integer endpoints of the numerical range and each integer between the two endpoints. For example, "C1-C10 alkyl" means an alkyl group having 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10 carbon atoms.
[0100] In the present invention, When R is selected from a single bond, express Indicates that the attachment site of the substituent R is not limited.
[0101] In the present invention, "*" indicates a linking site.
[0102] In the present invention, "halogen" or "halo" refers to -F, -Cl, -Br or -I.
[0103] In the present invention, the term "alkyl" refers to a monovalent residue formed by the loss of a hydrogen atom from a saturated hydrocarbon containing a primary (normal) carbon atom, a secondary carbon atom, a tertiary carbon atom, a quaternary carbon atom, or a combination thereof. A phrase containing the term, for example, "C1-C10 alkyl" refers to an alkyl containing 1 to 10 carbon atoms, and each occurrence may be independently C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl, C7 alkyl, C8 alkyl, C9 alkyl or C10 alkyl. Suitable examples include, but are not limited to, methyl (Me, -CH3), ethyl (Et, -CH2CH3), 1-propyl (n-Pr, n-propyl, -CH2CH2CH3), 2-propyl (i-Pr, i-propyl, -CH(CH3)2), 1-butyl (n-Bu, n-butyl, -CH2CH2CH2CH3), 2-methyl-1-propyl (i-Bu, i-butyl, -CH2CH(CH3)2), 2-butyl (s-Bu, s-butyl, -CH(C H3)CH2CH3), 2-methyl-2-propyl (t-Bu, t-butyl, -C(CH3)3), 1-pentyl (n-pentyl, -CH2CH2CH2CH2CH3), 2-pentyl (-CH(CH3)CH2CH2CH3), 3-pentyl (-CH(CH2CH3)2), 2-methyl-2-butyl (-C(CH3)2CH2CH3), 3-methyl-2-butyl (-CH(CH3)CH(CH3)2), 3-methyl-1-butyl (- CH2CH2CH(CH3)2), 2-methyl-1-butyl (-CH2CH(CH3)CH2CH3), 1-hexyl (-CH2CH2CH2CH2CH2CH3), 2-hexyl (-CH(CH3)CH2CH2CH2CH3), 3-hexyl (-CH(CH2CH3)(CH2CH2CH3)), 2-methyl-2-pentyl (-C(CH3)2CH2CH2CH3), 3-methyl-2-pentyl (-CH(CH3)CH( 2), 2-methyl-3-pentyl (-CH(CH2CH3)CH(CH3)2), 2,3-dimethyl-2-butyl (-C(CH3)2CH(CH3)2), 3,3-dimethyl-2-butyl (-CH(CH3)C(CH3)3 and octyl (-(CH2)7CH3).
[0104] In the present invention, "haloalkyl" refers to an alkyl group substituted with one or more halogen (chlorine, fluorine, bromine or iodine) atoms. Polyhaloalkyl groups have the same or mixed types of halogen atoms. "Perhaloalkyl" refers to an alkyl group in which each hydrogen atom is replaced by a halogen atom. A haloalkyl group in which a particular carbon atom is "completely halogenated" means that all hydrogen atoms attached to that carbon are replaced by halogen atoms. Representative mono-, di- and trihaloalkyl groups include: chloromethyl, chloroethyl, bromomethyl, bromoethyl, iodomethyl, iodoethyl, chloropropyl, bromopropyl, iodopropyl, 1,1-dichloromethyl, 1,1-dibromomethyl, 1,1-dichloropropyl, 1,2-dibromopropyl, 2,3-dibromopropyl, 1-chloro-2-bromoethyl, 2-chloro-3-bromopropyl, trifluoromethyl, trichloromethyl, etc. It is understood that "fluoroalkyl" refers to an alkyl group substituted with one or more fluorine atoms.
[0105] In the present invention, "cycloalkyl" refers to a non-aromatic hydrocarbon containing ring carbon atoms, which can be a monocyclic alkyl, a spirocyclic alkyl, or a bridged cycloalkyl. Phrases containing this term, for example, "C3-C10 cycloalkyl" refers to a cycloalkyl containing 3 to 10 carbon atoms, each occurrence of which can be independently C3 cycloalkyl, C4 cycloalkyl, C5 cycloalkyl, C6 cycloalkyl, C7 cycloalkyl, C8 cycloalkyl, C9 cycloalkyl or C10 cycloalkyl. Suitable examples include, but are not limited to, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl and cycloheptyl. In addition, "cycloalkyl" may also contain one or more double bonds, and representative examples of cycloalkyl containing double bonds include cyclopentenyl, cyclohexenyl, cyclohexadienyl and cyclobutadienyl.
[0106] In the present invention, the "number of ring atoms" refers to the number of atoms in the atoms constituting the ring itself of a structural compound (e.g., a monocyclic compound, a condensed ring compound, a cross-linked compound, a carbocyclic compound, a heterocyclic compound) formed by atoms bonding to form a ring. When the ring is substituted by a substituent, the atoms contained in the substituent are not included in the ring atoms. The same is true for the "number of ring atoms" described below unless otherwise specified. For example, the number of ring atoms of a benzene ring is 6, the number of ring atoms of a naphthalene ring is 10, and the number of ring atoms of a biphenyl is 12.
[0107] In the present invention, the term "aryl, aromatic group or aromatic group" refers to a hydrocarbon group containing at least one aromatic ring, such as: benzene, naphthalene, anthracene, fluoranthene, phenanthrene, triphenylene, dinaphthylen, tetracene, pyrene, benzopyrene, acenaphthene, fluorene, diphenyl, terphenyl and derivatives of the above aromatic groups.
[0108] In the present invention, the term "arylene" refers to an aromatic hydrocarbon group derived from an aromatic ring compound by removing two hydrogen atoms, which may be a monocyclic arylene, a condensed ring arylene, or a polycyclic arylene. For polycyclic rings, at least one is an aromatic ring system. For example, "C6-C10 arylene" refers to an arylene containing 6 to 10 carbon atoms, and each occurrence may be independently C6 arylene, C7 arylene, C8 arylene, C9 arylene or C10 arylene. Suitable examples include, but are not limited to, phenylene, biphenylene, naphthalene, anthracene, phenanthrene, perylene, triphenylene and their derivatives.
[0109] In the present invention, the term "cycloalkylene" refers to a hydrocarbon group having two monovalent group centers derived from a cycloalkyl group by removing two hydrogen atoms, and may be a monocycloalkylene group, a spirocycloalkylene group, or a bridged cycloalkylene group. For example, "C3-C10 cycloalkylene" refers to a cycloalkylene group containing 3 to 9 carbon atoms, and each occurrence may be independently C3 cycloalkylene, C4 cycloalkylene, C5 cycloalkylene, C6 cycloalkylene, C7 cycloalkylene, C8 cycloalkylene or C9 cycloalkylene. Suitable examples include, but are not limited to, cyclopropylene, cyclobutylene, cyclopentylene, cyclohexylene and cycloheptylene. In addition, "cycloalkylene" may also contain one or more double bonds, and representative examples of cycloalkylene groups containing double bonds include cyclopentenylene, cyclohexenylene, cyclohexadienylene and cyclobutadienylene.
[0110] In the present invention, "substituted" means that a hydrogen atom in a substituted group is replaced by a substituent.
[0111] In the present invention, "substituted or unsubstituted" means that the defined group may be substituted or unsubstituted. When the defined group is substituted, it should be understood that the defined group may be substituted by one or more substituents R, wherein R is selected from but not limited to: deuterium atom, cyano, isocyano, nitro or halogen, alkyl containing 1 to 9 C atoms, cycloalkyl containing 3 to 9 C atoms, -NR'R", silane, carbonyl, alkoxycarbonyl, aryloxycarbonyl, carbamoyl, haloformyl, formyl, isocyanate, thiocyanate, isothiocyanate, hydroxyl, trifluoromethyl, and the above groups may be further substituted by substituents acceptable in the art; it is understood that R' and R" in -NR'R" are independently selected from but not limited to: H, deuterium atom, cyano, isocyano, nitro or halogen, alkyl containing 1 to 9 C atoms, cycloalkyl containing 3 to 9 C atoms.
[0112] The temperature parameters in the present invention, if not specifically limited, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0113] In the present invention, "double-layer composite polyimide material" refers to a composite polyimide material structure including a first layer and a second layer stacked in sequence; the first layer comprises thermoplastic polyimide; and the second layer comprises transparent polyimide. "Three-layer composite polyimide material" refers to a composite polyimide material structure including a first layer, a second layer and a third layer stacked in sequence; the first layer and the third layer independently comprise thermoplastic polyimide; and the second layer comprises transparent polyimide.
[0114] The detailed description of the present invention is as follows:
[0115] The invention provides a multilayer composite polyimide material with high optical transparency, a thermal expansion coefficient matching that of a copper foil, and high bonding strength with the copper foil.
[0116] The technical solution is as follows:
[0117] A multi-layer composite polyimide material, the structure of which includes a first layer and a second layer arranged in layers;
[0118] The first layer comprises a thermoplastic polyimide;
[0119] The second layer comprises transparent polyimide;
[0120] The thermoplastic polyimide has a structure shown in formula (1-1):
[0121]
[0122] Z is an alkyl group;
[0123] X is
[0124] R1 is selected from a single bond or a group as shown below:
[0125]
[0126] Each R2 is independently selected from non-existent, chain alkyl, cycloalkyl, fluoroalkyl, ester or halogen;
[0127] Y is selected from the group shown below:
[0128]
[0129] R3, R5 and R6 are independently selected from non-existent, chain alkyl, cycloalkyl, fluoroalkyl, ester or halogen; R4 and R7 are independently selected from a single bond or a group as shown below:
[0130] *O*
[0131]
[0132] The structural unit of the transparent polyimide has a structure shown in formula (2-1):
[0133]
[0134] in,
[0135] Ar1 is selected from any of the following groups:
[0136]
[0137] R8 and R9 are each independently selected from a single bond or a group as shown below:
[0138]
[0139] and at least one of R8 and R9 is R 10 and R 11 Each is independently selected from non-existent, chain alkyl, cycloalkyl, fluoroalkyl, ester or halogen;
[0140] Ar3 is an alicyclic ring having 6 to 20 ring atoms, or an aromatic ring having 6 to 20 ring atoms;
[0141] Ar2 is selected from any of the following groups:
[0142]
[0143]
[0144] Each R 12 Each is independently selected from non-existent, chain alkyl, cycloalkyl, fluoroalkyl, ester or halogen;
[0145] Each R 13 Each is independently selected from the following groups:
[0146] *O*
[0147] M is selected from *O* or *S*;
[0148] m represents the degree of polymerization;
[0149] n, p and r are each independently selected from any integer between 1 and 10.
[0150] * indicates the attachment site.
[0151] The molecular chain end of the thermoplastic polyimide shown in formula (1-1) contains an alkyl group and a specific amide group, so that the bonding strength between the thermoplastic polyimide and the copper foil or the transparent polyimide layer is very high, and the thermoplastic polyimide also has excellent dielectric properties, thereby improving the bonding properties and dielectric properties of the multilayer composite polyimide material. The thermoplastic transparent polyimide TCPI of the present invention has a light transmittance T% higher than 87% @ 360nm ~ 780nm, a glass transition temperature of 150 ° C ~ 250 ° C, a 5% thermal decomposition temperature of more than 340 ° C, a low dielectric constant (<2.5) and a low dielectric loss (<0.01), and belongs to a class of colorless and transparent thermoplastic polyimide that can be heated and melted.
[0152] In the present invention, Z is an alkyl group, which is mainly related to the bonding properties and dielectric properties of the thermoplastic polyimide and the multilayer composite polyimide material.
[0153] In one embodiment, Z is a C1-C20 straight chain alkyl, a C1-C20 branched chain alkyl or a C3-C20 cycloalkyl. Further, Z is a C2-C18 straight chain alkyl, a C2-C18 branched chain alkyl or a C3-C18 cycloalkyl. Further, Z is a C4-C18 straight chain alkyl, a C4-C18 branched chain alkyl or a C4-C18 cycloalkyl.
[0154] In one embodiment, Z is ethyl, propyl, isopropyl, n-butyl, isobutyl, pentyl, isopentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl or cyclohexyl.
[0155] In the present invention, X is It is mainly related to the transparency, glass transition temperature, heat resistance, thermal expansion coefficient and dimensional stability of thermoplastic polyimide.
[0156] In one embodiment, R1 is selected from a single bond.
[0157] In one embodiment, R1 is selected from any of the following groups:
[0158]
[0159] In one embodiment, each R2 is independently selected from C1-C10 straight chain alkyl, C1-C10 branched chain alkyl, C3-C10 cycloalkyl, C1-C10 fluoroalkyl or halogen. Further, each R2 is independently selected from methyl (-CH3), ethyl, 1-propyl, 2-propyl, 1-butyl, 2-methyl-1-propyl, 2-butyl, 2-methyl-2-propyl, 2-pentyl, 3-pentyl, 2-methyl-2-butyl, 3-methyl-2-butyl, 3-methyl-1-butyl, 2-methyl-1-butyl, 1-hexyl, 2-hexyl, 3-hexyl, 2-methyl-2-pentyl, 3-methyl-2-pentyl, 4-methyl-2-pentyl, 3-methyl-3-pentyl, 2-methyl-3-pentyl, 2,3-dimethyl-2-butyl, 3,3-dimethyl-2-butyl, n-octyl, cyclohexyl, cyclooctyl, adamantyl, trifluoromethyl (-CF3) or fluorine (-F). Further, each R2 is independently selected from -F, -CH3 or -CF3.
[0160] In the present invention, Y is selected from the following groups:
[0161]
[0162] p and r are each independently selected from any integer between 1 and 10.
[0163] In one embodiment, R3, R5 and R6 are independently selected from C1-C10 straight chain alkyl, C1-C10 branched chain alkyl, C3-C10 cycloalkyl, C1-C10 fluoroalkyl or halogen. Further, R3, R5 and R6 are independently selected from methyl (-CH3), ethyl, 1-propyl, 2-propyl, 1-butyl, 2-methyl-1-propyl, 2-butyl, 2-methyl-2-propyl, 2-pentyl, 3-pentyl, 2-methyl-2-butyl, 3-methyl-2-butyl, 3-methyl-1-butyl, 2-methyl-1-butyl, 1-hexyl, 2-hexyl, 3-hexyl, 2-methyl-2-pentyl, 3-methyl-2-pentyl, 4-methyl-2-pentyl, 3-methyl-3-pentyl, 2-methyl-3-pentyl, 2,3-dimethyl-2-butyl, 3,3-dimethyl-2-butyl, n-octyl, cyclohexyl, cyclooctyl, adamantyl, trifluoromethyl (-CF3) or fluorine (-F). Furthermore, R3, R5 and R6 are independently selected from -F, -CH3 or -CF3.
[0164] In the present invention, p is selected from any integer from 1 to 10, i.e., 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.
[0165] In the present invention, r is selected from any integer between 1 and 10, i.e., 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.
[0166] In the present invention, the polyimide molecule shown in formula (2-1) contains amide bonds and fluorene structures. The amide bonds can form hydrogen bonds between molecular chains, thereby forming a hydrogen bond cross-linked network, promoting the in-plane orientation of the molecular chains and enhancing the interaction between the molecular chains, thereby reducing the thermal expansion coefficient, increasing the glass transition temperature, and improving the transparency and dimensional stability of the polyimide; the fluorene group with a large steric hindrance effect can increase the rotational kinetic energy of the polyimide molecular chain, limit the movement of the chain segments, greatly increase the glass transition temperature, and improve the transparency and dimensional stability of the polyimide. According to tests, the transmittance T% of the transparent polyimide CPI of the present invention is higher than 85% @360nm~780nm, and the glass transition temperature T g Above 300°C, the coefficient of thermal expansion (CTE) is 10-25 ppm / °C.
[0167] In the present invention, Ar1 contains at least one amide bond, which is mainly related to the transparency, glass transition temperature, thermal expansion coefficient, heat resistance and dimensional stability of the polyimide. Specifically, Ar1 is selected from any of the following groups:
[0168]
[0169] R8 and R9 are each independently selected from a single bond or a group as shown below:
[0170]
[0171] and at least one of R8 and R9 is
[0172] R 10 and R 11 Each is independently selected from non-existent, chain alkyl, cycloalkyl, fluoroalkyl, ester or halogen;
[0173] Ar3 is an alicyclic ring having 6 to 20 ring atoms, or an aromatic ring having 6 to 20 ring atoms.
[0174] In one embodiment, the R 10 and R 11 are independently selected from C1-C10 straight chain alkyl, C1-C10 branched chain alkyl, C3-C10 cycloalkyl, C1-C10 fluoroalkyl or halogen. 10 and R 11 Each is independently selected from -F, CH3 or -CF3.
[0175] In one embodiment, Ar3 is an alicyclic ring having 6 to 20 ring atoms, including but not limited to an alicyclic ring having 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 ring atoms, preferably cyclohexane.
[0176] In one embodiment, Ar3 is an aromatic ring having 6 to 20 ring atoms, including but not limited to an aromatic ring having 6, 10, 12, 14, 16, 18 or 20 ring atoms, preferably a benzene ring, a naphthalene ring, a biphenyl ring or a terphenyl ring.
[0177] In the present invention, Ar2 contains at least one fluorene group, which is mainly related to the transparency, glass transition temperature, and dimensional stability of the polyimide. Specifically, Ar2 is selected from any of the following groups:
[0178]
[0179] Each R 12 Each is independently selected from non-existent, chain alkyl, cycloalkyl, fluoroalkyl, ester or halogen;
[0180] Each R 13 Each is independently selected from the following groups:
[0181]
[0182] M is selected from *O* or *S*;
[0183] In one embodiment, each R 12 are independently selected from C1-C10 straight chain alkyl, C1-C10 branched chain alkyl, C3-C10 cycloalkyl, C1-C10 fluoroalkyl or halogen. 12 Each is independently selected from -F, CH3 or -CF3.
[0184] In the present invention, m is the degree of polymerization, and is from 1 to 1000. Further, m is from 10 to 500. Further, m is from 10 to 300. Further, m is from 50 to 300.
[0185] In one embodiment, the thickness of the first layer is 1 μm to 20 μm, and the thickness of the second layer is 30 μm to 100 μm.
[0186] Figure 1 Schematic diagram of the structure of a double-layer composite polyimide material shown in one embodiment of the present invention, wherein 101 represents a first layer comprising thermoplastic polyimide (hereinafter referred to as the thermoplastic polyimide layer), and 102 represents a second layer comprising transparent polyimide (hereinafter referred to as the transparent polyimide layer).
[0187] In one of the embodiments, the multi-layer composite polyimide material further includes a third layer;
[0188] Along a direction away from the first layer, the third layer and the second layer are stacked;
[0189] The third layer comprises the thermoplastic polyimide represented by the above formula (1-1).
[0190] The inventors have found that by designing a multilayer composite polyimide material into a "sandwich" type, the structure of which includes a first layer, a second layer and a third layer arranged in a stacked manner, the first layer and the third layer independently contain the thermoplastic polyimide shown in the above formula (1-1), and the second layer contains a transparent polyimide whose structural unit is the formula (2-1). This can enable the multilayer composite polyimide material to have excellent heat resistance, matching the thermal expansion properties of copper foil, and high bonding strength with the copper foil, as well as good dimensional stability. Using the above-mentioned multilayer composite polyimide material for the preparation of adhesive-type copper clad laminates can more effectively reduce the thickness of traditional adhesive-type copper clad laminates, and solve the problems of delamination and bubbles in the copper clad laminates during soldering and high-temperature applications.
[0191] It can be understood that the thermoplastic polyimide contained in the first layer and the second layer only needs to satisfy the general formula (1-1), and the specific types of the thermoplastic polyimide contained in the first layer and the second layer are not required to be completely consistent, that is, the specific types of the thermoplastic polyimide contained in the first layer and the second layer can be the same or different. In addition, the thermoplastic polyimide shown in formula (1-1) has been described above and will not be repeated here.
[0192] In one embodiment, the thickness of the third layer is 1 μm to 20 μm.
[0193] Figure 2 Schematic diagram of the structure of a three-layer composite polyimide material according to an embodiment of the present invention, wherein 201 represents a first layer comprising thermoplastic polyimide, 202 represents a second layer comprising transparent polyimide, and 203 represents a third layer comprising thermoplastic polyimide.
[0194] The present invention also provides a method for preparing the multilayer composite polyimide material as described above, comprising the following steps:
[0195] A diamine having a structure of formula (I), a primary amine having a structure of formula (II) and a dianhydride having a structure of formula (III) are mixed in a first organic solvent, subjected to a first polymerization reaction, and subjected to dehydration and cyclization to prepare a thermoplastic polyimide represented by formula (1-1);
[0196] H2N-Y-NH2(I), Z-NH2(II),
[0197] Mixing a diamine having a structure of formula (IV) and a dianhydride having a structure of formula (V) in a second organic solvent, performing a second polymerization reaction, and performing dehydration cyclization to prepare a transparent polyimide having a structural unit having a structure represented by formula (2-1);
[0198] H2N-Ar2-NH2(IV),
[0199] Performing composite molding treatment on the transparent polyimide and the thermoplastic polyimide;
[0200] Ar1, Ar2, X, Y and Z are as defined above.
[0201] S100 prepares the thermoplastic polyimide shown in formula (1-1):
[0202] It can be understood that X is the dianhydride residue obtained from polyimide TCPI, Y is the diamine residue obtained from polyimide TCPI, and Z is an end group containing a linear, branched or alicyclic alkyl group, and the introduction of the end group can effectively improve the dielectric properties and adhesiveness of TPCI.
[0203] It is understandable that the present invention has no particular restrictions on the preparation method of the thermoplastic polyimide shown in the above formula (1-1), and it can be synthesized by a commonly known method, such as a one-step heating method or a two-step chemical method. Among them, the one-step heating method refers to a dibasic acid anhydride and a diamine with a set molar ratio, which are heated to a temperature of 50°C to 200°C (preferably 100°C to 180°C) in an organic solvent for a condensation reaction of usually about 0.1h to 12h (preferably 0.1h to 5h) to obtain the thermoplastic polyimide TCPI. The two-step chemical method refers to the preparation of polyamic acid by the reaction of a monomer dianhydride and a monomer diamine, and the reaction of dehydrating and cyclizing the amic acid to form an imide by adding a chemical dehydrating agent. The chemical dehydrating agent can be selected from acetic anhydride and benzoic anhydride. In addition, an organic base such as pyridine or triethylamine can be used for catalysis.
[0204] In the present invention, the organic solvent used to prepare the thermoplastic polyimide is an organic solvent that can dissolve the product and can adapt to the required temperature when heated. Such solvents include non-protonic polar solvents such as dimethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone, dimethyl sulfoxide, cyclopentane, triethylene glycol dimethyl ether, etc.; ketone solvents such as cyclohexanone and butanone; phenolic solvents such as m-cresol, phenol, chlorophenol; aromatic solvents such as toluene and xylene. The organic solvent can be a combination of one or more of the above solvents. In the above reaction, known chemical dehydrating agents and catalysts can also be used. As chemical dehydrating agents, for example, acetic anhydride, benzoic anhydride, etc. can be cited, and two or more can also be combined. As catalysts, for example, tertiary amines such as triethylamine, dimethylaniline, pyridine, picoline, isoquinoline, etc. can also be combined with two or more.
[0205] Preferably, the present invention prepares the thermoplastic polyimide represented by formula (1-1) by a one-step heating method. The technical scheme is as follows:
[0206] A method for preparing a thermoplastic polyimide as shown in formula (1-1), comprising the following steps:
[0207] A diamine having a structure of formula (I), a primary amine having a structure of formula (II) and a dianhydride having a structure of formula (III) are mixed in a first organic solvent, subjected to a first polymerization reaction, and subjected to dehydration and cyclization to prepare a thermoplastic polyimide represented by formula (1-1);
[0208] H2N-Y-NH2(I), Z-NH2(II),
[0209] In one embodiment, the diamine having the structure of formula (I) is selected from the diamine compounds shown below:
[0210]
[0211] In one embodiment, the primary amine having the structure of formula (II) is preferably a primary amine having 1 to 20 carbon atoms, and more preferably a primary amine having 4 to 18 carbon atoms.
[0212] In one embodiment, the primary amine having the structure of formula (II) is selected from ethylamine, propylamine, isopropylamine, n-butylamine, isobutylamine, 2-aminobutane, 2-amino-2-methylpropane, pentylamine, isopentylamine, n-hexylamine, n-heptylamine, n-octylamine, n-nonylamine, n-decylamine, 1-aminododecane, n-tridecylamine, stearylamine, 2-cyclohexylethylamine or (3-aminopropyl)cyclohexane.
[0213] In one embodiment, the primary amine having the structure of formula (II) is selected from any of the following primary amines:
[0214]
[0215] In one embodiment, the dianhydride having the structure of formula (III) is selected from the dianhydride compounds shown below:
[0216]
[0217] In one embodiment, the molar ratio of the diamine having the structure of formula (I) to the primary amine having the structure of formula (II) is (90-99):(1-10), and the total molar amount of the diamine having the structure of formula (I) and the primary amine having the structure of formula (II) is 100;
[0218] The molar ratio of the total molar amount of the diamine having the structure of formula (I) and the primary amine having the structure of formula (II) to the dianhydride having the structure of formula (III) is 100:(100-110).
[0219] In one embodiment, the temperature of the first polymerization reaction is 50° C. to 200° C., and the time is 0.1 h to 12 h.
[0220] S200: Preparing a transparent polyimide having a structural unit having a structure shown in formula (2-1)
[0221] It is understandable that the present invention has no particular limitation on the method for preparing the above-mentioned polyimide, and it can be synthesized by a commonly known method, such as a method for preparing the polyimide by solution polymerization of a monomer dianhydride and a monomer diamine by a known conventional polyimide, a method of mixing the monomer dianhydride and the monomer diamine in an organic solvent and reacting the mixture can be easily implemented, such as a one-step heating method or a two-step chemical method.
[0222] In one embodiment, the organic solvent is selected from one or more mixtures of N,N-dimethylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, meta-cresol, N-methyl caprolactam, cyclopentane, dimethyl sulfoxide (DMSO), cyclohexanone, hexamethylphosphoramide and gamma-butyrolactone. That is, these solvents can be used alone or in combination of two or more. In addition, within the scope of obtaining a homogeneous solution, even a solvent that does not dissolve polyamic acid can also be added to the above-mentioned solvent.
[0223] It is understandable that in the present invention, diamine is dissolved or dispersed in an organic solvent in a slurry state to prepare a diamine solution, and dianhydride is added to the diamine solution. In addition, tetracarboxylic dianhydride can be added in a solid state or in a state dissolved or dispersed in an organic solvent in a slurry state.
[0224] The polyimide is prepared by dehydration cyclization imidization of polyamic acid. The dehydration cyclization imidization reaction is not particularly limited and can be thermal imidization or chemical imidization. As with conventional polyamic acid, the imidization reaction can be carried out by using a known dehydration reaction using heating or chemical cyclization method.
[0225] Among them, (1) the heating method can be used to gradually increase the temperature from 80° C. to 400° C. to carry out the imidization reaction of the amic acid dehydration cyclization to form imide.
[0226] (2) The chemical cyclization imidization method is to react the amic acid to form an imide by dehydrating and cyclizing the amic acid by adding a chemical dehydrating agent. The chemical dehydrating agent can be selected from acetic anhydride and benzoic anhydride. An organic base such as pyridine or triethylamine can be used for catalysis. The reaction temperature can be -20°C to 200°C. In this reaction, the polymer solution of polyamic acid can be used without change, or can be diluted. The solution containing polyimide obtained in this way can be used, or can be used in the following way: using a solvent such as methanol or ethanol to precipitate the polymer and then separate it in the form of powder, or redissolving the obtained powder in an appropriate solvent before use. The present invention has no particular limitation on the solvent used for redissolution, as long as it can dissolve the obtained polymer, such as one or a mixture of several selected from m-cresol, N,N-dimethylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, cyclohexanone and γ-butyrolactone.
[0227] Preferably, the present invention prepares the transparent polyimide shown in formula (2-1) according to a two-step chemical method. The technical scheme is as follows:
[0228] A method for preparing a transparent polyimide as shown in formula (2-1), comprising the following steps:
[0229] A diamine having a structure of formula (IV) and a dianhydride having a structure of formula (V) are mixed in a second organic solvent, a second polymerization reaction is carried out, and a transparent polyimide having a structural unit having a structure shown in formula (2-1) is prepared by chemical cyclization and imidization;
[0230] H2N-Ar2-NH2(IV),
[0231] In one embodiment, the diamine having the structure of formula (IV) is selected from the diamine compounds shown below:
[0232]
[0233] Optionally, the diamine compound shown below may be added together to prepare a transparent polyimide having a structural unit having a structure shown in formula (2-1):
[0234]
[0235] In one embodiment, the dianhydride having the structure of formula (V) is selected from the dianhydride compounds shown below:
[0236]
[0237]
[0238] Preferably, the dianhydride having the structure of formula (V) is a structure having multiple aromatic rings directly and linearly connected, which can enable the polyimide to form a nearly planar structure, which is beneficial to the close stacking of the polyimide molecular chains, thereby reducing the free volume and thermal expansion coefficient, while giving the polyimide film excellent mechanical properties.
[0239] Optionally, the dianhydride compound shown below may be added together to prepare a transparent polyimide having a structural unit having a structure shown in formula (2-1):
[0240]
[0241] In one embodiment, the molar ratio of the diamine having the structure of formula (IV) to the dianhydride having the structure of formula (V) is (95-105): 100. Preferably, the molar ratio is close to 100:100, and the molecular weight of the obtained polyamic acid and subsequent polyimide is relatively large. Furthermore, the molar ratio of the diamine having the structure of formula (IV) to the dianhydride having the structure of formula (V) is 100:100.
[0242] The present invention has no particular limitation on the temperature and time of the polymerization reaction for preparing transparent polyimide, which are preferably below 60° C., more preferably 0° C. to 50° C., and the reaction time is 10 minutes to 30 hours, preferably 0.1 h to 5 h.
[0243] In one embodiment, the chemical dehydrating agent used in the chemical cycloimidation is selected from acetic anhydride or benzoic anhydride.
[0244] In one embodiment, the catalyst used in the chemical cycloimidation is selected from pyridine or triethylamine.
[0245] In one embodiment, the reaction temperature of the chemical cyclization imidization is -20°C to 200°C.
[0246] S300: Composite molding of the transparent polyimide and the thermoplastic polyimide
[0247] In one embodiment, the composite molding process is cast coating, and the multilayer composite polyimide material is preferably in the form of a film.
[0248] In one embodiment, the composite molding process comprises the following steps:
[0249] preparing a thermoplastic polyimide solution;
[0250] coating the thermoplastic polyimide solution on the surface of the transparent polyimide;
[0251] drying.
[0252] Thermoplastic polyimide TCPI solution is coated on one side or both sides of the transparent polyimide CPI film, and the dry film thickness of the coating TCPI is 1 μm to 20 μm. There is no particular restriction on the heating and drying temperature and duration, as long as the solvent is removed, for example, the temperature can be 100° C. to 150° C., and the drying time can be 5 min to 60 min.
[0253] The multi-layer composite polyimide material (composite film) formed by coating and drying can be used as an insulating adhesive material for transparent circuit boards, such as rigid printed circuit boards (PCBs), flexible printed circuit boards (FPCs) and their multi-layer circuit boards. Specifically:
[0254] The present invention also provides an insulating base film, which comprises the multi-layer composite polyimide material as described above.
[0255] The present invention also provides a copper clad laminate, which comprises the multi-layer composite polyimide material as described above, or the insulating base film as described above.
[0256] In one of the embodiments, the copper foil in the copper clad laminate is distributed on a single side of the multi-layer composite polyimide material.
[0257] In one embodiment, the copper foil of the copper clad laminate is distributed on one side of the multi-layer composite polyimide material, and the multi-layer composite polyimide material is a double-layer composite polyimide material. The structural schematic diagram of the copper clad laminate can be seen in Figure 3 , wherein 301 is a copper foil, 302 is a thermoplastic polyimide layer, and 303 is a transparent polyimide layer.
[0258] In one embodiment, the copper foil of the copper clad laminate is distributed on both sides of the multi-layer composite polyimide material, and the multi-layer composite polyimide material is a three-layer composite polyimide material. The structural schematic diagram of the copper clad laminate can be seen in Figure 4 , wherein 401 and 405 are copper foils, 402 and 404 are thermoplastic polyimide layers, and 403 is a transparent polyimide layer.
[0259] The present invention also provides a method for preparing the copper clad laminate as described above, comprising the following steps:
[0260] Copper foil is laminated on one side or both sides of the multi-layer composite polyimide material to form a single-sided or double-sided adhesive-free copper clad laminate.
[0261] In one embodiment, the pressing temperature is 180°C to 300°C.
[0262] The present invention also provides a rigid printed circuit board, which comprises the multi-layer composite polyimide material as described above, or the insulating base film as described above, or the copper-clad board as described above.
[0263] The present invention also provides a flexible printed circuit board, which comprises the multi-layer composite polyimide material as described above, or the insulating base film as described above, or the copper-clad board as described above.
[0264] The following are specific embodiments.
[0265] The raw materials and reagents involved in the following specific examples can be obtained from commercial sources, or can be prepared by those skilled in the art according to known methods.
[0266] The testing method of the present invention is as follows:
[0267] ① Coefficient of thermal expansion (CTE): TMA Q400 static thermomechanical analyzer (TMA) was used to characterize the thermal dimensional change behavior of the polyimide film. The test was conducted in a nitrogen atmosphere with a temperature range of 50-300°C, a fixed load of 0.05N, a heating rate of 5°C / min, and before the test, the sample was heated to 300°C to eliminate residual stress.
[0268] ②Optical transmittance: Shimadzu UV-2550 ultraviolet visible spectrometer, average transmittance at wavelengths of 360 to 780 nm.
[0269] ③ Glass transition temperature (Tg): DSC Perkin-Elmer DSC-7 was used to test the polyimide film, nitrogen was used, and the heating rate was 10°C / min.
[0270] ④Thermogravimetric analysis (TGA): TGA Perkin-Elemer TGA-2 tests polyimide film, nitrogen, 50-700°C, heating rate of 10°C / min.
[0271] ⑤ Dielectric property test (Dk, Df): PNA-N5244A model vector network analyzer was used to characterize the dielectric properties of the polyimide film using the resonant cavity mode at a frequency of 10 GHz.
[0272] ⑥Testing of copper clad laminate:
[0273] Peel strength: using TA-630 peel strength tester (CECO) in accordance with IPC-TM650 standard.
[0274] Solder resistance: soldering furnace, in accordance with IPC-TM650 2.4.13 standard.
[0275]
[0276]
[0277] The synthesis of T-1 to T-4 refers to CN 202011386779.7.
[0278]
[0279] Example 1
[0280] This embodiment provides a transparent polyimide and a preparation method thereof, a thermoplastic polyimide and a preparation method thereof, and a copper clad laminate and a preparation method thereof. The details are as follows:
[0281] Add 2,2'-bis(trifluoromethyl)diaminobiphenyl to the reaction vessel (2.5618g, 0.008mol) and N-1 compound (0.6928g, 0.002mol), dimethylacetamide (42.5g), control the temperature at 5℃, and stir to dissolve. Add dianhydride T1 compound (1.0117g, 0.003mol) and 3,3',4,4'-biphenyltetracarboxylic dianhydride (2.0595g, 0.007mol) in batches, and polymerize for 12h in a nitrogen atmosphere to form a transparent polyamide acid solution. Add acetic anhydride (7.2g) and triethylamine (2.25g) to the polymerization system and continue the reaction for 24h. Slowly pour the reaction mixture into ethanol, precipitate a white filamentous precipitate, filter it out, and dry it to obtain a transparent polyimide resin. Dissolve this resin in dimethylacetamide to form a 20% mass fraction solution, apply it on a glass plate, place it in an oven and heat it to 280℃ to form a transparent polyimide CPI film.
[0282] 1,4-cyclohexanedimethylamine (0.2844 g, 0.002 mol), 2,2'-bis(trifluoromethyl)diaminobiphenyl (2.5618 g, 0.008 mol), dimethylformamide (19.2 g) and cyclohexanone (20.5 g) were added to the reaction container and stirred to dissolve. 3,4,3',4'-biphenyltetracarboxylic dianhydride (3.0893 g, 0.0105 mol) was added, the temperature was raised to 180°C for reaction for 3 h, and after cooling to room temperature, n-butylamine (0.0731 g, 0.001 mol) was added, the temperature was raised to 140°C for reaction for 5 h, and a thermoplastic polyimide solution TCPI was obtained.
[0283] 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (0.2360 g) and dispersant BYK-333 (0.0053 g) were added to the above TCPI solution, and after mechanical stirring, the mixture was coated on both sides of the polyimide CPI base film, heated at 120°C for 15 min, and the copper foil of the corresponding size was attached to both sides of the above film, placed in a fast press machine for preheating at 180°C for 20 s, and then pressed at a pressure of 12 MPa for 180 s; placed in an oven at 210±10°C for 45 min, and the sample Cu / TCPI / CPI / TCPI / Cu was obtained. Among them, the thickness of the copper foil was 12.5 μm, the thickness of the CPI film was 50 μm, and the thickness of the TCPI was 5 μm.
[0284] Example 2
[0285] This embodiment provides a transparent polyimide and a preparation method thereof, a thermoplastic polyimide and a preparation method thereof, and a copper clad laminate and a preparation method thereof. The details are as follows:
[0286] Add 2,2'-bis(trifluoromethyl)diaminobiphenyl (1.6011 g, 0.005 mol), N-2 compound (1.7321 g, 0.005 mol), and N-methyl-2-pyrrolidone (24.3 g) to the reaction container, control the temperature not to exceed 20°C, and stir to dissolve. Add dianhydride T2 compound (4.1072 g, 0.009 mol) and pyromellitic dianhydride (0.2181 g, 0.001 mol) in batches, and polymerize for 20 hours in a nitrogen atmosphere to form a transparent polyamic acid solution. Apply the polymerized solution on a glass plate, place it in an oven, and heat it from 50°C to 250°C to form a transparent polyimide CPI film.
[0287] 1,3-cyclohexanedimethylamine (0.1422 g, 0.001 mol), 2,2'-bis(trifluoromethyl)diaminobiphenyl (2.8820 g, 0.009 mol), N-methyl-2-pyrrolidone (16.8 g) and toluene (19.1 8) were added to the reaction container and stirred to dissolve. 4,4'-oxydiphthalic anhydride (3.1641 g, 0.0102 mol) was added, the temperature was raised to 150°C for reaction for 8 h, and after cooling to room temperature, isopentylamine (0.0348 g, 0.0004 mol) was added, the temperature was raised to 160°C for reaction for 7 h, and a thermoplastic polyimide solution TCPI was obtained.
[0288] 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (0.3527 g) and dispersant BYK-333 (0.0048 g) were added to the above TCPI solution system, and after mechanical stirring, they were coated on both sides of the polyimide CPI base film, heated at 150°C for 3 minutes, and the corresponding size of copper foil was attached to both sides of the above film, placed in a fast press machine for preheating at 180°C for 20 seconds, and then pressed at a pressure of 10MPa for 120 seconds; placed in a 200±10°C oven for baking for 30 minutes, and the sample Cu / TCPI / CPI / TCPI / Cu was obtained. Among them, the thickness of the copper foil is 12.5μm, the thickness of the CPI film is 76μm, and the thickness of the TCPI is 10μm.
[0289] Example 3
[0290] This embodiment provides a transparent polyimide and a preparation method thereof, a thermoplastic polyimide and a preparation method thereof, and a copper clad laminate and a preparation method thereof. The details are as follows:
[0291] Add 1,4-cyclohexanediamine (0.3425 g, 0.003 mol), N-3 compound (4.7793 g, 0.007 mol), and cyclopentane sulfone (45.2 g) to the reaction container, control the temperature at 0°C, and stir to dissolve. Add dianhydride T3 compound (2.4030 g, 0.007 mol) and hexafluorodianhydride (1.3327 g, 0.003 mol) in batches, and polymerize for 15 hours in a nitrogen atmosphere to form a transparent polyamic acid solution. Apply the polymerized solution on a glass plate, place it in an oven, and heat it from 25°C to 300°C in a gradient manner to form a transparent polyimide CPI film.
[0292] 1,4-cyclohexanedimethylamine (0.2844 g, 0.002 mol), 2,2'-bis(trifluoromethyl)diaminobiphenyl (2.5618 g, 0.008 mol), dimethylformamide (20.3 g) and xylene (20.6 g) were added to the reaction container and stirred to dissolve. Bisphenol A diether dianhydride (5.5692 g, 0.0107 mol) was added, the temperature was raised to 175°C for reaction for 5 h, and after cooling to room temperature, n-octylamine (0.1809 g, 0.0014 mol) was added, the temperature was raised to 180°C for reaction for 3 h, and a thermoplastic polyimide solution TCPI was obtained.
[0293] 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (0.2624 g) and dispersant BYK-333 (0.0054 g) were added to the above TCPI solution system, and after mechanical stirring, they were coated on both sides of the polyimide CPI base film, heated at 115°C for 8 minutes, and copper foils of corresponding sizes were attached to both sides of the above film, placed in a fast press machine for preheating at 190°C for 10 seconds, and then pressed at a pressure of 10MPa for 250 seconds; placed in an oven at 180±10°C for 60 minutes to obtain the sample Cu / TCPI / CPI / TCPI / Cu. Among them, the thickness of the copper foil is 12.5μm, the thickness of the CPI film is 88μm, and the thickness of the TCPI is 15μm.
[0294] Example 4
[0295] This embodiment provides a transparent polyimide and a preparation method thereof, a thermoplastic polyimide and a preparation method thereof, and a copper clad laminate and a preparation method thereof. The details are as follows:
[0296] Add 2,2-bis(4-aminophenyl)hexafluoropropane (0.3345g, 0.001mol) and N-3 compound (6.1435g, 0.009mol) and dimethylacetamide (46.8g) to the reaction vessel, control the temperature at 30°C, and stir to dissolve. Add dianhydride T4 compound (2.3120g, 0.005mol) and 3,3',4,4'-biphenyltetracarboxylic dianhydride (1.4711g, 0.005mol) in batches, and polymerize for 11h in a nitrogen atmosphere to form a transparent polyamic acid solution. Add acetic anhydride (10.6g) and triethylamine (3.9g) to the polymerization system and continue the reaction for 6h. Slowly pour the reaction mixture into ethanol, precipitate a white filamentous precipitate, filter it out, and dry it to obtain a transparent polyimide resin. The resin was dissolved in dimethylacetamide to form a 20% mass fraction solution, which was coated on a glass plate and placed in an oven and heated to 250° C. to form a transparent polyimide CPI film.
[0297] Add hydrogenated biphenyl diamine (0.9816 g, 0.005 mol), 2,2'-bis(trifluoromethyl)diaminobiphenyl (1.6011 g, 0.005 mol), dimethylformamide (20.2 g) and cyclohexanone (25.5 g) to the reaction vessel and stir to dissolve. Add bisphenol A type diether dianhydride (4.1639 g, 0.01 mol) and 3,3',4,4'-biphenyltetracarboxylic dianhydride (0.5884 g, 0.002 mol) and react at 0°C for 24 h. Add acetic anhydride (10.9 g) and triethylamine (4.8 g) to the polymerization system and continue to react for 24 h. Continue to add stearic acid amine (1.0780g, 0.004mol) to the system, heat to 160℃ and react for 5h, slowly pour the reaction mixture into ethanol, precipitate white filamentous precipitate, filter out, dry to obtain polyimide resin. Dissolve the resin in dimethylacetamide to obtain thermoplastic polyimide solution TCPI.
[0298] 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (0.3134 g) and dispersant BYK-333 (0.0062 g) were added to the above polyimide solution system, and after mechanical stirring, they were coated on both sides of the polyimide CPI base film, heated at 115°C for 5 minutes, and copper foils of corresponding sizes were attached to both sides of the above film, placed in a fast press machine for preheating at 180°C for 20 seconds, and then pressed at a pressure of 15MPa for 100 seconds; placed in an oven at 190±10°C for 60 minutes to obtain the sample Cu / TCPI / CPI / TCPI / Cu. Among them, the thickness of the copper foil is 12.5μm, the thickness of the CPI film is 100μm, and the thickness of the TCPI is 12μm.
[0299] Example 5
[0300] This embodiment provides a transparent polyimide and a preparation method thereof, a thermoplastic polyimide and a preparation method thereof, and a copper clad laminate and a preparation method thereof. The details are as follows:
[0301] Add 2,2'-bis(trifluoromethyl)diaminobiphenyl (1.6011 g, 0.005 mol), N-4 compound (3.7639 g, 0.005 mol), and dimethylacetamide (37.8 g) to the reaction vessel, control the temperature at 22°C, and stir to dissolve. Add dianhydride T1 compound (2.6979 g, 0.008 mol) and pyromellitic dianhydride (0.4362 g, 0.002 mol) in batches, and polymerize for 8 hours in a nitrogen atmosphere to form a transparent polyamide acid solution. Add acetic anhydride (15.5 g) and triethylamine (4.2 g) to the polymerization system, and continue the reaction for 18 hours. Slowly pour the reaction mixture into ethanol, precipitate a white filamentous precipitate, filter it out, and dry it to obtain a transparent polyimide resin. The resin was dissolved in dimethylacetamide to form a 20% mass fraction solution, which was coated on a glass plate and placed in an oven and heated to 270° C. to form a transparent polyimide CPI film.
[0302] Add Pramine 1075 (0.5370 g, 0.001 mol), 2,2'-bis(trifluoromethyl)diaminobiphenyl (2.8820 g, 0.009 mol) and dimethyl sulfoxide (41.8 g) to the reaction container and stir to dissolve. Add 4,4'-oxydiphthalic anhydride (3.5674 g, 0.0115 mol), heat to 190°C and react for 6 h. After cooling to room temperature, add 2-cyclohexylethylamine (0.3817 g, 0.003 mol), heat to 165°C and react for 4 h to obtain thermoplastic polyimide solution TCPI.
[0303] 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (0.3517 g) and dispersant BYK-333 (0.0091 g) were added to the above TCPI solution system, and after mechanical stirring, they were coated on both sides of the polyimide CPI base film, heated at 100°C for 20 minutes, and copper foils of corresponding sizes were attached to both sides of the above film, placed in a fast press machine for preheating at 180°C for 10 seconds, and then pressed at a pressure of 12MPa for 300 seconds; placed in an oven at 180±10°C for 60 minutes to obtain the sample Cu / TCPI / CPI / TCPI / Cu. Among them, the thickness of the copper foil is 12.5μm, the thickness of the CPI film is 95μm, and the thickness of the TCPI is 2μm.
[0304] Example 6
[0305] This embodiment provides a transparent polyimide and a preparation method thereof, a thermoplastic polyimide and a preparation method thereof, and a copper clad laminate and a preparation method thereof. The details are as follows:
[0306] Add 2,2'-bis(trifluoromethyl)diaminobiphenyl (1.9214 g, 0.006 mol), N-1 compound (1.3856 g, 0.004 mol), and N-methyl-2-pyrrolidone (22.8 g) to the reaction container, control the temperature at 18°C, and stir to dissolve. Add dianhydride T2 compound (2.2817 g, 0.005 mol) and pyromellitic dianhydride (1.0906 g, 0.005 mol) in batches, and polymerize for 10 hours in a nitrogen atmosphere to form a transparent polyamic acid solution. Apply the polymerized solution on a glass plate, place it in an oven, and heat it from 20°C to 290°C with a gradient temperature increase to form a transparent polyimide CPI film.
[0307] Add Pramine 1075 (0.2685 g, 0.0005 mol), 2,2'-bis(trifluoromethyl)diaminobiphenyl (3.0421 g, 0.0095 mol) and N-methyl-2-pyrrolidone (45.6 g) to the reaction container and stir to dissolve. Add (4-phthalic anhydride) formyloxy-4-phthalate (3.6527 g, 0.0108 mol), heat to 155°C and react for 10 h. After cooling to room temperature, add n-heptylamine (0.1843 g, 0.0016 mol), heat to 150°C and react for 9 h to obtain thermoplastic polyimide solution TCPI.
[0308] 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (0.3269 g) and dispersant BYK-333 (0.0033 g) were added to the above TCPI solution system, and after mechanical stirring, they were coated on both sides of the polyimide CPI base film, heated at 105°C for 12 minutes, and copper foils of corresponding sizes were attached to both sides of the above film, placed in a fast press machine for preheating at 180°C for 20 seconds, and then pressed at a pressure of 10MPa for 190 seconds; placed in an oven at 180±10°C for 60 minutes to obtain the sample Cu / TCPI / CPI / TCPI / Cu. Among them, the thickness of the copper foil is 12.5μm, the thickness of the CPI film is 67μm, and the thickness of the TCPI is 18μm.
[0309] Example 7
[0310] This embodiment provides a transparent polyimide and a preparation method thereof, a thermoplastic polyimide and a preparation method thereof, and a copper clad laminate and a preparation method thereof. The details are as follows:
[0311] Add hydrogenated benzyl diamine (0.5890 g, 0.003 mol), N-2 compound (2.4249 g, 0.007 mol), N-methyl-2-pyrrolidone (44.8 g) to the reaction container, control the temperature at 40°C, and stir to dissolve. Add dianhydride T1 compound (2.6979 g, 0.008 mol) and cyclobutanetetracarboxylic dianhydride (0.3922 g, 0.002 mol) in batches, and polymerize for 12 hours in a nitrogen atmosphere to form a transparent polyamic acid solution. Apply the polymerized solution on a glass plate, place it in an oven, and heat it from 50°C to 300°C to form a transparent polyimide CPI film.
[0312] 1,3-cyclohexanedimethylamine (0.3556 g, 0.0025 mol), 2,2'-bis(trifluoromethyl)diaminobiphenyl (2.4017 g, 0.0075 mol), N-methyl-2-pyrrolidone (27.8 g) and phenol (19.5) were added to the reaction container and stirred to dissolve. 4,4'-oxydiphthalic anhydride (3.6294 g, 0.0117 mol) was added, the temperature was raised to 180°C and reacted for 11 hours, and after cooling to room temperature, stearic acid amine (0.9163 g, 0.0034 mol) was added, the temperature was raised to 160°C and reacted for 5 hours to obtain a thermoplastic polyimide solution TCPI.
[0313] 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (0.2847 g) and dispersant BYK-333 (0.0039 g) were added to the above TCPI solution system, and after mechanical stirring, they were coated on both sides of the polyimide CPI base film, heated at 105°C for 20 minutes, and copper foils of corresponding sizes were attached to both sides of the above film, placed in a fast press machine for preheating at 170°C for 20 seconds, and then pressed at a pressure of 12MPa for 480 seconds; placed in a 250±10°C oven for baking for 35 minutes, and the sample Cu / TCPI / CPI / TCPI / Cu was obtained. Among them, the thickness of the copper foil is 12.5μm, the thickness of the CPI film is 92μm, and the thickness of the TCPI is 20μm.
[0314] Example 8
[0315] Add hydrogenated benzyl diamine (0.5890 g, 0.003 mol), N-2 compound (2.4249 g, 0.007 mol), N-methyl-2-pyrrolidone (44.8 g) to the reaction container, control the temperature at 40°C, and stir to dissolve. Add dianhydride T1 compound (2.6979 g, 0.008 mol) and cyclobutanetetracarboxylic dianhydride (0.3922 g, 0.002 mol) in batches, and polymerize for 12 hours in a nitrogen atmosphere to form a transparent polyamic acid solution. Apply the polymerized solution on a glass plate, place it in an oven, and heat it from 50°C to 300°C to form a transparent polyimide CPI film.
[0316] 1,3-cyclohexanedimethylamine (0.3556 g, 0.0025 mol), 2,2'-bis(trifluoromethyl)diaminobiphenyl (2.4017 g, 0.0075 mol), N-methyl-2-pyrrolidone (27.8 g) and phenol (19.5) were added to the reaction container and stirred to dissolve. 4,4'-oxydiphthalic anhydride (3.6294 g, 0.0117 mol) was added, the temperature was raised to 180°C and reacted for 11 hours, and after cooling to room temperature, stearic acid amine (0.9163 g, 0.0034 mol) was added, the temperature was raised to 160°C and reacted for 5 hours to obtain a thermoplastic polyimide solution TCPI.
[0317] 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (0.2847 g) and dispersant BYK-333 (0.0039 g) were added to the above TCPI solution system, and after mechanical stirring, the mixture was coated on the polyimide CPI base film, heated at 105°C for 20 min, and the copper foil of the corresponding size was attached to the surface of the above film, placed in a fast press machine for preheating at 170°C for 20 s, and then pressed at a pressure of 12 MPa for 480 s; placed in a 250±10°C oven for baking for 35 min, and the sample Cu / TCPI / CPI was obtained. The thickness of the copper foil was 12.5 μm, the thickness of the CPI film was 56 μm, and the thickness of the TCPI was 2.5 μm.
[0318] Comparative Example 1
[0319] This comparative example provides a transparent polyimide and a preparation method thereof, a thermoplastic polyimide and a preparation method thereof, and a copper clad laminate and a preparation method thereof. The details are as follows:
[0320] Add 2,2'-bis(trifluoromethyl)diaminobiphenyl (3.2023g, 0.01mol) and dimethylacetamide (35.8g) to the reaction vessel, control the temperature at 25°C, and stir to dissolve. Add dianhydride T1 compound (1.0117g, 0.003mol) and 3,3',4,4'-biphenyltetracarboxylic dianhydride (2.0595g, 0.007mol) in batches, and polymerize for 24 hours in a nitrogen atmosphere to form a transparent polyamide acid solution. Add acetic anhydride (8.6g) and triethylamine (3.2g) to the polymerization system and continue the reaction for 12 hours. Slowly pour the reaction mixture into ethanol, precipitate a white filamentous precipitate, filter it out, and dry it to obtain a transparent polyimide resin. Dissolve this resin in dimethylacetamide to form a 20% mass fraction solution, apply it on a glass plate, place it in an oven and heat it to 250°C to form a transparent polyimide CPI film.
[0321] 1,4-cyclohexanedimethylamine (0.2844 g, 0.002 mol), 2,2'-bis(trifluoromethyl)diaminobiphenyl (2.5618 g, 0.008 mol), dimethylformamide (15.7 g) and cyclohexanone (17.1 g) were added to the reaction container and stirred to dissolve. 3,4,3',4'-biphenyltetracarboxylic dianhydride (2.9422 g, 0.01 mol) was added and the temperature was raised to 170°C for reaction for 7 hours to obtain a thermoplastic polyimide solution TCPI.
[0322] 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (0.2540 g) and dispersant BYK-333 (0.0063 g) were added to the above polyimide solution system, and after mechanical stirring, they were coated on both sides of the polyimide CPI base film, heated at 130°C for 10 minutes, and copper foils of corresponding sizes were attached to both sides of the above film, placed in a fast press machine for preheating at 180°C for 20 seconds, and then pressed at a pressure of 10MPa for 120 seconds; placed in a 200±10°C oven and baked for 60 minutes to obtain the sample Cu / TCPI / CPI / TCPI / Cu. Among them, the thickness of the copper foil is 12.5μm, the thickness of the CPI film is 55μm, and the thickness of the TCPI is 7μm.
[0323] Comparative Example 2
[0324] This comparative example provides a transparent polyimide and a preparation method thereof, a thermoplastic polyimide and a preparation method thereof, and a copper clad laminate and a preparation method thereof. The details are as follows:
[0325] Add 2,2'-bis(trifluoromethyl)diaminobiphenyl (3.2023 g, 0.01 mol) and N-methyl-2-pyrrolidone (25.8 g) to the reaction container, control the temperature not to exceed 30°C, and stir to dissolve. Add dianhydride T1 compound (3.0352 g, 0.009 mol) and pyromellitic dianhydride (0.2181 g, 0.001 mol) in batches, and polymerize for 15 hours in a nitrogen atmosphere to form a transparent polyamic acid solution. Apply the polymerized solution on a glass plate, place it in an oven, and heat it from 50°C to 300°C by gradient heating to form a transparent polyimide CPI film.
[0326] 1,3-cyclohexanedimethylamine (0.1422 g, 0.001 mol), 2,2'-bis(trifluoromethyl)diaminobiphenyl (2.8820 g, 0.009 mol), N-methyl-2-pyrrolidone (16.8 g) and toluene (19.1 8) were added to the reaction container and stirred to dissolve. 4,4'-oxydiphthalic anhydride (3.1021 g, 0.01 mol) was added and the temperature was raised to 160°C for reaction for 10 hours to obtain a thermoplastic polyimide solution TCPI.
[0327] 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (0.3247 g) and dispersant BYK-333 (0.0055 g) were added to the above polyimide solution system, and after mechanical stirring, they were coated on both sides of the polyimide CPI base film, heated at 150°C for 5 minutes, and copper foils of corresponding sizes were attached to both sides of the above film, placed in a fast press machine for preheating at 200°C for 20 seconds, and then pressed at a pressure of 12MPa for 240 seconds; placed in an oven at 220±10°C for 30 minutes to obtain the sample Cu / TCPI / CPI / TCPI / Cu. Among them, the thickness of the copper foil is 12.5μm, the thickness of the CPI film is 60μm, and the thickness of the TCPI is 8μm.
[0328] 1. The performance characterization results of the polyimide prepared in each embodiment and comparative example are shown in Table 1 below:
[0329] Table 1
[0330]
[0331]
[0332] As can be seen from Table 1, the thermoplastic transparent polyimide TCPI of the present invention has a transmittance higher than 87% @ 360nm ~ 780nm, a glass transition temperature of 150 ℃ ~ 250 ℃, a 5% thermal decomposition temperature of more than 340 ℃, a low dielectric constant (<2.5) and a low dielectric loss (<0.01), and belongs to a class of colorless transparent thermoplastic polyimide that can be heated and melted. Compared with Comparative Examples 1 and 2, the CPI containing a fluorene-based structure prepared in Examples 1 to 8 has a higher glass transition temperature (Tg> 390 ℃) and stronger heat resistance. Compared with Comparative Examples 1 and 2, the use of primary amine-terminated TCPI as the adhesive layer of the copper clad laminate, and the mutual cooperation with the transparent polyimide having a structure shown in formula (2-1) in the structural unit, can make the copper clad laminate have a lower dielectric constant (≤2.5) and a lower dielectric loss (<0.01)
[0333] 2. The performance characteristics of the copper clad laminates prepared in each embodiment and comparative example are shown in Table 2 below:
[0334] Table 2
[0335] Group Peel strength Solder resistance(℃) Example 1 1.28 365 Example 2 1.29 360 Example 3 1.31 355 Example 4 1.34 360 Example 5 1.39 345 Example 6 1.37 355 Example 7 1.32 345 Example 8 1.29 345 Comparative Example 1 1.27 355 Comparative Example 2 1.24 365
[0336] It can be seen from Table 2 that, compared with Comparative Examples 1 and 2, using primary amine-terminated TCPI as the adhesive layer of the copper clad laminate can make the copper clad laminate have higher peel strength (>1.2N / mm) and higher heat resistance (soldering temperature resistance>340°C).
[0337] The technical features of the above-mentioned implementation modes and examples can be combined in any appropriate manner. To make the description concise, not all possible combinations of the technical features in the above-mentioned implementation modes and examples are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0338] The above-described embodiments only express several implementation methods of the present invention, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, without departing from the concept of the present invention, several variations and improvements can be made, which all belong to the protection scope of the present invention. In addition, it should be understood that after reading the above-mentioned teaching content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and the equivalent forms obtained also fall within the protection scope of the present invention. It should also be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided by the present invention are all within the protection scope of the claims attached to the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims, and the description and drawings may be used to explain the contents of the claims.
Claims
1. A multilayer composite polyimide material, characterized in that: Its structure includes a first layer and a second layer which are stacked; The first layer comprises a thermoplastic polyimide; The second layer comprises transparent polyimide; The thermoplastic polyimide has a structure shown in formula (1-1): Z is an alkyl group; X is R1 is selected from a single bond or a group as shown below: Each R2 is independently selected from non-existent, chain alkyl, cycloalkyl, fluoroalkyl, ester or halogen; Y is selected from the group shown below: R3, R5 and R6 are independently selected from non-existent, chain alkyl, cycloalkyl, fluoroalkyl, ester or halogen; R4 and R7 are independently selected from a single bond or a group as shown below: The structural unit of the transparent polyimide has a structure shown in formula (2-1): in, Ar1 is selected from any of the following groups: R8 and R9 are each independently selected from a single bond or a group as shown below: and at least one of R8 and R9 is R 10 and R 11 Each is independently selected from non-existent, chain alkyl, cycloalkyl, fluoroalkyl, ester or halogen; Ar3 is an alicyclic ring having 6 to 20 ring atoms, or an aromatic ring having 6 to 20 ring atoms; Ar2 is selected from any of the following groups: Each R 12 Each is independently selected from non-existent, chain alkyl, cycloalkyl, fluoroalkyl, ester or halogen; Each R 13 Each is independently selected from the following groups: M is selected from *O* or *S*; m represents the degree of polymerization; p and r are independently selected from any integer from 1 to 10; * indicates the attachment site.
2. The multilayer composite polyimide material according to claim 1, characterized in that: Z is a C1-C20 straight chain alkyl group, a C1-C20 branched chain alkyl group or a C3-C20 cycloalkyl group.
3. The multilayer composite polyimide material according to claim 1, characterized in that: The R2, R3, R5 and R6 are independently selected from C1-C10 straight-chain alkyl, C1-C10 branched-chain alkyl, C3-C10 cycloalkyl, C1-C10 fluoroalkyl or halogen.
4. The multilayer composite polyimide material according to claim 1, characterized in that: The R 10 , R 11 and R 12 Each is independently selected from C1-C10 straight-chain alkyl, C1-C10 branched-chain alkyl, C3-C10 cycloalkyl, C1-C10 fluoroalkyl or halogen.
5. The multilayer composite polyimide material according to claim 1, characterized in that: Ar3 is a benzene ring, a naphthalene ring or a cyclohexane ring.
6. The multilayer composite polyimide material according to any one of claims 1 to 5, characterized in that: m ranges from 1 to 1000.
7. The multilayer composite polyimide material according to any one of claims 1 to 5, characterized in that: The thickness of the first layer is 1 μm to 20 μm, and the thickness of the second layer is 30 μm to 100 μm.
8. The multilayer composite polyimide material according to any one of claims 1 to 5, characterized in that: Also includes the third layer; Along a direction away from the first layer, the third layer and the second layer are stacked; The third layer comprises the thermoplastic polyimide according to any one of claims 1 to 7.
9. The multilayer composite polyimide material according to claim 8, characterized in that: The thickness of the third layer is 1 μm to 20 μm.
10. A method for preparing the multilayer composite polyimide material according to any one of claims 1 to 9, characterized in that: The steps include: A diamine having a structure of formula (I), a primary amine having a structure of formula (II) and a dianhydride having a structure of formula (III) are mixed in a first organic solvent, subjected to a first polymerization reaction, and subjected to dehydration and cyclization to prepare a thermoplastic polyimide represented by formula (1-1); H2N-Y-NH2(I)、Z-NH2(II)、 Mixing a diamine having a structure of formula (IV) and a dianhydride having a structure of formula (V) in a second organic solvent, performing a second polymerization reaction, and performing dehydration cyclization to prepare a transparent polyimide having a structural unit having a structure represented by formula (2-1); H2N-Ar2-NH2(IV)、 Performing composite molding treatment on the transparent polyimide and the thermoplastic polyimide; Ar1, Ar2, X, Y and Z are as defined in claims 1 to 9.
11. The method for preparing a multilayer composite polyimide material according to claim 10, characterized in that: The molar ratio of the diamine having the structure of formula (I) to the primary amine having the structure of formula (II) is: (90-99): (1-10); The molar ratio of the total molar amount of the diamine having the structure of formula (I) and the primary amine having the structure of formula (II) to the dianhydride having the structure of formula (III) is 100:(100-110); and / or The temperature of the first polymerization reaction is 50° C. to 200° C., and the time is 0.1 h to 12 h.
12. The method for preparing a multilayer composite polyimide material according to claim 10, characterized in that: The diamine having the structure of formula (I) is selected from the diamine compounds shown below: and / or The primary amine having the structure of formula (II) is selected from ethylamine, propylamine, isopropylamine, n-butylamine, isobutylamine, 2-aminobutane, 2-amino-2-methylpropane, pentylamine, isopentylamine, n-hexylamine, n-heptylamine, n-octylamine, n-nonylamine, n-decylamine, 1-aminododecane, n-tridecylamine, stearylamine, 2-cyclohexylethylamine or (3-aminopropyl)cyclohexane; and / or The dianhydride having the structure of formula (III) is selected from the dianhydride compounds shown below:
13. The method for preparing a multilayer composite polyimide material according to claim 10, characterized in that: The molar ratio of the diamine having the structure of formula (IV) to the dianhydride having the structure of formula (V) is (95-105):100; and / or The temperature of the second polymerization reaction is below 60° C., and the time is 0.1 h to 30 h.
14. The method for preparing a multilayer composite polyimide material according to claim 10, characterized in that: The diamine having the structure of formula (IV) is selected from the diamine compounds shown below: The dianhydride having the structure of formula (V) is selected from the dianhydride compounds shown below:
15. The method for preparing a multilayer composite polyimide material according to any one of claims 10 to 14, characterized in that: The composite molding process comprises the following steps: preparing a thermoplastic polyimide solution; coating the thermoplastic polyimide solution on the surface of the transparent polyimide; drying.
16. An insulating base film, characterized in that: A multilayer composite polyimide material comprising the multilayer composite polyimide material according to any one of claims 1 to 9, or a multilayer composite polyimide material prepared according to the preparation method according to any one of claims 10 to 15.
17. A copper clad laminate, characterized in that: A multilayer composite polyimide material comprising any one of claims 1 to 9, or a multilayer composite polyimide material prepared by the preparation method according to any one of claims 10 to 15, or an insulating base film according to claim 16.
18. A rigid printed circuit board, characterized in that: A multilayer composite polyimide material comprising any one of claims 1 to 9, or a multilayer composite polyimide material prepared according to the preparation method according to any one of claims 10 to 15, or an insulating base film according to claim 16, or a copper clad laminate according to claim 17.
19. A flexible printed circuit board, characterized in that: A multilayer composite polyimide material comprising any one of claims 1 to 9, or a multilayer composite polyimide material prepared according to the preparation method according to any one of claims 10 to 15, or an insulating base film according to claim 16, or a copper clad laminate according to claim 17.
Citation Information
Patent Citations
An amide dianhydride, its preparation method and application
CN112625017B
Polyimide, preparation method thereof, polyimide film and application
CN115232309A
Multilayered polyimide film and laminated polyimide film with metal layer using it
JP2006068986A